Valine-Resistant Escherichia coli K-12 Strains with Mutations in the ilvB Operon - Sutton, Ann (1981)
Escherichia coli K-12 mutants resistant to growth inhibition by valine were isolated. These strains contained mutations in the ilvB operon effecting either the regulation of acetohydroxy acid synthase I or the sensitivity of the enzyme to end product inhibition by valine.